The WTO Dispute Settlement System and How It Incentivizes Imparity Between Indonesia's Executive and Parliament - Sjahputra, Muhammad Raihan; Jesse Christian Holwerda (Universitas Airlangga, 2024)
The Indonesian zeitgeist to provide more checks toward the power of its executive organ to formulate and enter into international treaties and agreements during the infancy phase of the Reformasi era, which was spurred on by the international debt ballooning that they suffered under the leadership of President Soeharto, was somewhat undermined by the passing of the Law No. 24 of 2000, which effectively limits the involvement of the House in the formulation process of international treaties to which Indonesia would be a party to. This apparently voluntary weakening of the legislative's oversight function is caused by the understanding that the realities of contemporary international intercourse has resulted in the increasing need for the formulation and entrance into international treaties and agreements as expeditiously as possible. The WTO, as the manifestation of globalization and its byproduct, neoliberalism, plays a role in creating such a necessity, which in turn incentivizes the imparity between the legislative and executive branches of the Indonesian government. The focus of this article is its dispute settlement system, and how its strengths and its weaknesses, has created the incentive for negotiations and expeditious decision making outside of the system itself, which requires a considerable degree of latitude to be afforded to the party involved in such negotiations, the executive. The discussion in this paper delves upon works dealing with the theoretical implications of several aspects of the WTO dispute settlement system and a case study of the US-Clove Cigarettes Case, which perfectly demonstrates said implications toward Indonesia.